Urgensi Undang-Undang Pelayanan Publik dan Pencegahan Fungsi Diskresi untuk Penyalahgunaan Kekuasaan - Thontowi, Jawahir (Unisia, 2016)
Public Service Law is not merely important, but also useful to sthrengten a good governance and clean government in Indonesia. To make the Public Service Law is an effective legal instrument, it is required to consider several steps. The first is dealt with the important effort to make theoretical review, establish a comprehensive research, identify main problems and spesify a scope of public servant competency. The second is concerned with efforts of finding relevant arguments on public service that the Indonesian Constitusion 1945, the MPR Decree 1998, the Local Authonomy Law Number 22/1999 have indeed contributed in significant to support the Draft of Public Service Law come into existence. Finally, the Draft of PSL disfunctions to stop the abusive of power or detoumement de pouveir (corruption, collusion, and nepotism) takes place if the Indonesian government fails to control the application of the government discretion over the rule of law.